Permissibility of wakaf in the provision of affordable housing - Abdul Rashid, Khairuddin; Hasan, Sharina Farihah; Mohd Fauzi, Puteri Nur Farah Naadia; Ahmad Sarkawi, Azila; Aripin, Srazali; Mansor, Nur Syaimasyaza (American Scientific Publishers, 2018)
Many poor and needy Muslims face problem of access to decent and affordable housing. In Islam the practice of wakaf, a form of endowment, is omnipresent. Wakaf authorities are known to have, under their guardianship, endowed assets, properties and cash yet these have not been utilized strategically to address the said housing problem. The purpose of the study is to determine the permissibility, from the perspective of the Shariah, of wakaf assets, properties and cash to be utilized to develop affordable housing. The study employed the desk research and interview methods. The outcome from the study suggests there is no known Shariah ruling to prevent such an endeavor and some wakaf authorities have already commissioned housing projects utilizing wakaf assets, properties and cash. The study identified key fatwas (rulings) relating to the permissibility of developing housing projects on wakaf land and issues arising therefrom and the ensuing strategies. The findings is contributing towards enhancing the understanding of personnel of the Wakaf authorities and Shariah policy makers on how wakaf assets, properties and cash could be better utilized in addressing the housing woes of needy Muslims and others.